(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted to investigate the potential factors effects on hydrogen peroxide bacterial spores killing severity. This study was achieved in Dairy Science and Technology Department , Food Sciences College, Al-Qasim Green University, Babylon, Iraq, during (2022 2023). Itincluded an experiment evaluation of the effect of 0.01, 0.05, and 0.1% concentrations of hydrogen peroxide at temperature of 35 degrees Celsius during an incubation time of 10, 20, 40, and 80 minutes. After that, the number of bacteria was measured by the plate counting method. The treatments were subjected to heat treatmentsat temperatures of 85, 90, and 95 degrees Celsius with and without added Hydrogen Peroxide for 20 minutes. The results showed that 0.1% Hydrogen Peroxide concentration eliminated entirely vegetative Bacillus bacteria and its spores. The results also indicated the concentration of 0.05%.and Heat treatment 90 and 95 °C eliminated bacterial spores to the comparison to control treatment 4.5×410 Cfu.ml-1 raw milk. The results also show a concentration of 0.01%. with heat treatment at 85, 90, and 95°C reduced the number of bacteria, 45×102 , 35×102 Cfu.ml-1 raw milk, and 25×102, respectively, compared to the control treatment 4.5 ×104 Cfu.ml-1 raw milk.